2020
DOI: 10.1088/1742-6596/1469/1/012176
|View full text |Cite
|
Sign up to set email alerts
|

Effect of geometric parameters on the performance of motorcycle catalytic converters

Abstract: The critical environmental issues of the Indonesian automotive market growth are the increase in air pollution. Vehicle exhaust emission can cause significant problems for the human health and the environment. Therefore, vehicle emission control is indispensable to mitigate the environmental problem. One of the most widely used methods to reduce automotive emission is utilization of catalytic converter in exhaust system. In fact, the catalyst performance in the reduction of noxious gases depends on its materia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…A study by Lapisa et al [37] also showed that the geometric parameters significantly affect the conversion of HC and CO. They found that using folded perforated plates as a substrate resulted in good performance in terms of decreasing the HC (−93.6%) and CO (−0.56%) levels, as the zig-zag plate shape in their model increased the surface contact and intensity of the gas-catalyst collision.…”
Section: Substrate Design and Interaction With The Exhaust Systemmentioning
confidence: 96%
“…A study by Lapisa et al [37] also showed that the geometric parameters significantly affect the conversion of HC and CO. They found that using folded perforated plates as a substrate resulted in good performance in terms of decreasing the HC (−93.6%) and CO (−0.56%) levels, as the zig-zag plate shape in their model increased the surface contact and intensity of the gas-catalyst collision.…”
Section: Substrate Design and Interaction With The Exhaust Systemmentioning
confidence: 96%
“…In the environmental aspect, the impact of CO2 emissions from fossil burning, on the other hand, affects climate change which in turn will disrupt the ecosystem as a whole [5]. For this reason, it is necessary to save energy use and control environmental impacts in various fields with various methods, such as in the transportation sector [6], the industrial sector [7,8], and the building sector [9][10][11], etc. In addition to the commercial and residential sectors, the transportation sector is the three largest energy consumption sectors in Indonesia.…”
Section: Introductionmentioning
confidence: 99%